La familia y su incidencia en el desarrollo del lenguaje de los niños y niñas del primer año de educación básica de la escuela “José Ingenieros” de la ciudad de Loja. Período 2014 - 2015”. Lineamientos propositivos - Valarezo Tenorio, Mónica Alexandra (2016)
research work, refers to a study on: "FAMILY AND ITS IMPACT ON THE DEVELOPMENT OF LANGUAGE CHILDREN FIRST YEAR OF BASIC EDUCATION SCHOOL" JOSE ENGINEERS "CITY OF LOJA. PERIOD 2014-2015 ". GUIDELINES PROPOSITIONAL. of the city of Loja. PERIOD 2014-2015.Se structured and developed in accordance with the Rules of Academic System of the National University of Loja. The problem raised in this research is how the Family affects language development of children in the first year of basic Education School "José Ingenieros" of the city of Loja. Period 2014-2015?. an overall objective, it referred to the following is stated: To analyze the impact of the family in language development in children. The methods used were scientific, deductive, inductive and descriptive statistical model; The techniques used were: Survey, same as the Parents of Children First Year Education Center applied, in order to establish the types and ways of being of the Family; Plus an Observation was applied to children, First Year of School investigated; To evaluate the development of language. Taking into account the implementation of the Survey of Parents came to determine that: 42% of Parents believe that the kind of family you have is Nuclear; Extensive 29%, and 29% Parent. 25% Parents consider how to be your family corresponds to a family Rigid, 24% to a stable family, 20% to an overprotective family, 14% to a family centered on the Children, 12 permissive Family% to 5% of an unstable family. With regard to the results of the observation guide the children it is concluded that: 46% of children have reached Language Development Satisfactory, while 41% Very Satisfactory, and finally 13% it is unsatisfying.